The sixth man - Stearn, Jess (New York : Macfadden Book, 1961)
Fonds Suzan Daniel (FSD)
Titel op omslag: "One out every six men in America is a homosexual". This is the report of one of the most frightening surveys conducted since The Kinsey Books ; Fonds Suzan Daniel (FSD)F/02/016 Archief Roger Vertongen
Engels
Monografie